Potensi penerimaan retribusi pelayanan pasar dan kontribusi serta prospeknya terhadap pendapatan asli daerah kota samarinda - Dharma Hammam Nur Mubarok (Faculty of Economics and Business Mulawarman University, 2016)
The aim of this study is to find out the potency of market services retribution and its contribution and prospects as the source of district own source revenue in Samarinda. The source of this data is secondary data. The secondary data of this study are consisted of the realization report of district own source revenue in Samarinda, the report of the market service potency in Samarinda and the realization report of market services retribution in Samarinda by using descriptive statistic method. The used method of this study are analysis of market potential, analysis of the level of contribution and trend analysis. The result of this study shows that in first analysis, the calculation of market services potential retribution in Samarinda within a year indicates a great potential, but the realization of market service retribution in last five years still had not exceeded the total of existing potential, in the second analysis, the contribution of market services retributions as as the source of district own source revenue in Samarinda is placed on “very poor” indicator means that there was decreasing contributions in every years, and in the third analysis, the prospect of market services retribution in Samarinda shows positive result (increasing) for five years later.Keywords: Retributions, Own Source Revenue, Market Services